Getting students engaged - Phil Race (Association for Learning Development in Higher Education (ALDinHE), 2011)
We live and work in challenging times. Now that it seems certain (post Browne, 2010) that the fees students pay for their higher education experience will double (or worse), we can't be surprised that the emphasis on 'the student experience' of higher education will intensify. Whether students are saddling themselves with ever-increasing amounts of debt to afford that higher education experience, or whether it is parents who foot the bill, the spotlight continues to focus ever more sharply on student satisfaction, alongside all available measures of the quality of student engagement in higher education. We already have league tables in which the reflection of the student experience as gained from the National Student Survey features prominently. And with diminishing budgets for teaching, class sizes are likely to continue to grow - in those disciplines where higher education survives least scathed. So how can we meet the challenge of 'getting students engaged'?